The kingdom of Priam : Lesbos and the Troad between Anatolia and the Aegean - Ellis-Evans, Aneurin (Oxford classical monographs, 2019)
'The Kingdom of Priam' offers a detailed exploration of questions about regional integration in the ancient world through a diverse series of case studies focusing on the regional history of Lesbos and the Troad from the seventh century BC down to the first century AD.